Strategi Waria Mencari Nafkah di Kabupaten Sinjai - Ati Rukmana; Riri Amandaria (Jurnal Ekonomi dan Riset Pembangunan, 2023)
This study aims to determine the form of work, inhibiting factors, and transgender strategies in making a living in Sinjai Regency using descriptive qualitative research. The number of informants is 7 people with the criteria of adult transgender informants in Sinjai Regency who are willing to participate in providing complete and open information. Data collection through observation, interviews, and documentation were then analyzed through three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) The forms of work for transgender women in earning a living in Sinjai Regency are dominated by salon owners and employees, hairdressers, make-up artists (MUA), electron singers, and village consultative officials; (2) Factors inhibiting transgender women in earning a living in Sinjai Regency are: low education, lack of adequate skills and social stigma; and (3) Strategies for transgender people in Sinjai Regency to get a job, namely: (a) an active strategy in the form of taking courses on the work they are going to do, doing their own work activities, extending working hours, and doing more than one job; (b) Passive strategies, namely reducing spending and being indifferent to society's stigma; (c) network strategy in the form of building formal or informal relationships with the social and institutional environment and utilizing social media to get customers.